Energetics of Bacillus stearothermophilus growth: molar growth yield and temperature effects on growth efficiency. - Coultate, T P (1975)
The major growth yield of a prototrophic strain of Bacillus stearothermophilus under aerobic conditions on salts medium containing ammonium nitrate as the nitrogen source and glucose or succinate as the carbon source was maximal at the lowest growth temperature employed and decreased steadily as the temperature was raised. The temperature optima for growth yield and for growth rate were thus different. The molar growth yield values of the thermophile, especially at the lower growth temperatures, were similar to those reported for aerobically grown mesophilic bacteria, both on glucose and on succinate. At the higher growth temperatures, a lower proportion of glucose carbon was incorporated into cells and a correspondingly greater proportion was left incompletely utilized in the medium, mostly as acetate. This suggests a greater inefficiency in the coordination of the nonoxidative and oxidative phases of glucose metabolism at the gigher temperatures. Another factor causing a decreased cell yield at higher temperatures was possibly an uncoupling of energy production from respiration. The rates of respiration by intact cells of the thermophile on glucose and on succinate followed the Arrhenius relationship from 55 C to 20 C, which is some 20 C below the minimal growth temperature of the organism. The Arrhenius constant was 17.1 kcal/mol for glucose oxidation and 13.5 kcal/mol for succinate oxidation. These results are comparable to those reported for some mesophiles, and they suggest that the inability of the thermophile to grow at temperatures below about 41 C is not due to an abnormally high temperature coefficient for the uptake and oxidation of the carbon source.